Technical and Economic Analysis of a Solar PV Plant with a BESS and Green Hydrogen Storage in Sub-Saharan Africa: A Case Study of the Energy System of a Public Building in Burkina Faso - Alassane Kaboré; Adélaïde Lareba Ouedraogo; Kokou Prosper Semekonawo; Relwendé Quentin Ouedraogo; Florent Xavier Nignan; Bruno Korgo (Energies, 2026)
Reliable and sustainable electricity supply remains a major challenge for public infrastructure in Sub-Saharan Africa, where frequent grid interruptions and abundant solar resources create favorable conditions for hybrid renewable energy systems. This study presents a comprehensive techno-economic assessment of a hybrid photovoltaic–battery energy storage system–green hydrogen (PV–BESS–H2) system designed for a public administrative building in Ouagadougou, Burkina Faso. The system was evaluated using an annual building load profile together with locally measured solar irradiance and ambient temperature data. Dynamic simulations were performed in MATLAB/Simulink to assess the technical performance, energy flows, economic viability, and operational behavior of the proposed system. The selected configuration consists of a 77 kWp solar PV array, an 80 kWh lithium-ion battery, a 2 Nm3 h−1 electrolyzer, an 8.4 kg hydrogen storage tank, and a 10.6 kW fuel cell. Annual simulations show that the system generates 140.69 MWh of solar PV electricity and achieves a self-sufficiency ratio of 98.7% while limiting the unmet load to 1.3% of the annual electricity demand. Comparative analysis demonstrates that integrating battery and hydrogen storage substantially reduces the required storage capacities compared with standalone PV–BESS and PV–H2 configurations. The economic assessment yields a Levelized Cost of Electricity (LCOE) of USD 0.095 kWh−1 and a Levelized Cost of Hydrogen (LCOH) of USD 21.544 kg−1. Sensitivity analysis identifies the discount rate, solar PV investment cost, electrolyzer cost, and project lifetime as the principal drivers of the system’s economic performance. The results demonstrate that the complementary operation of battery and hydrogen storage can enhance the technical and economic performance of renewable energy systems of public buildings in regions with abundant solar resources while providing a practical framework for the design and evaluation of hybrid PV–BESS–H2 systems.